Third-Order Passive Filter Improvement for Renewable Energy Systems to Meet IEEE 519-1992 Standard Limits - Hojabri, Mojgan (2015)
Second and third-order passive filters (LC and LCL) are interesting filters used for grid-connected inverters. Due to the stability problems of this filter regarding resonance frequency, additional damping resistor suggested for an LCL filter. However, the resistor value has a considerable impact on the response of the filter, voltage and current harmonic distortion and system power loss. In this paper, the mathematic characteristics of LC, LCL filter, parallel and series connected damping LCL filters will be described with their design for PV grid-connected inverter. In this study optimal values used to meet IEEE 519-1992 standard limits for total harmonic distortion. Simulations are used to validate the theoretical analysis of the filters on filter performance and power quality of the grid ingrid-connected inverter.